Case Series of Testicular Tuberculosis in Calabar, South- South Nigeria (International Journal of Nursing Education, 2020)
Introduction: Bilateral testicular tuberculosis should be considered as an important differential of testicularswelling and scrotal ulcer in a country like Nigeria with high burden of tuberculosis infection.Case Reports: Here we present three cases of negroid male ranging in age from 39 years to 70 years whohad orchidectomy on account of testicular malignancy that turn out to be genital tuberculosis which wasdiagnosed histologically.Conclusion: Private medical practitioner in low income countries and in region of high tuberculosis burdenshould always have a high index of suspicions for tuberculosis in patients presenting with scrotal ulcers ortesticular swelling that fails to respond to antibiotics therapy. Adequate evaluation of patients with testicularswelling and ulcer by means of abdominal and scrotal ultrasound, bacteriological studies and PCR iscritical to diagnostic accuracy, optimal treatment and possibility of avoiding surgery in those with testiculartuberculosis and guiding against litigation.